Exploring the Higgs portal - Englert, Christoph; Plehn, Tilman; Zerwas, Dirk; Zerwas, Peter M. (Physics letters, 2011)
We study the Higgs portal from the Standard-Model to a hidden sector and examine which elements of the extended theory can be discovered and explored at the LHC. Our model includes two Higgs bosons covering parameter regions where the LHC will be sensitive to two, one or none of the particles at typical discovery luminosities for Standard Model Higgs production.
Gesehen am 29.04.2022